Kaluza–Klein gluon + jets associated production at the Large Hadron Collider - A.M. Iyer; F. Mahmoudi; N. Manglani; K. Sridhar (Physics Letters B, 2016)
The Kaluza–Klein excitations of gluons offer the exciting possibility of probing bulk Randall–Sundrum (RS) models. In these bulk models either a custodial symmetry or a deformation of the metric away from AdS is invoked in order to deal with electroweak precision tests. Addressing both these models, we suggest a new channel in which to study the production of KK-gluons (gKK): one where it is produced in association with one or more hard jets. The cross-section for the gKK + jets channel is significant because of several contributing sub-processes. In particular, the 1-jet and the 2-jet associated processes are important because at these orders in QCD the qg and the gg initial states respectively come into play. We have performed a hadron-level simulation of the signal and present strategies to effectively extract the signal from what could potentially be a huge background. We present results for the kinematic reach of the LHC Run-II for different gKK masses in bulk-RS models.